Job stress, work tension and job satisfaction of academics at a University of Technology - Maliwa, Ncumisa (Vaal University of Technology, 2020)
Until recently, the majority of the academics viewed the life of an academic as idyllic, autonomous and well protected. However, this scenario has since changed due to economic constraints and the reduction of government funding and funding from government agencies. Congruent to these transformations, technology advancements, students’ diversity, blended learning and the introduction of learning platforms has created further challenges in the way students learn and how modules are offered. It has become pivotal for academics to make contributions in the field of work through teaching and learning, community engagement, undertaking research activities, being part of staff training activities, performing administrative work, planning lectures, setting and marking of assessments providing feedback on academic performance, among other activities. These responsibilities often generate stress within the working environment. University academics face high stress levels that arise from persistent demands of academic life. This research drew from the confluence of the job demand control-support model and Herzberg’s motivation-hygiene theory. The research fits within a post-positivist quantitative paradigm whereby survey data was acquired from 250 academics from a university through a convenience sampling technique. A structured questionnaire encompassing the study constructs was used. Before data collection, a pilot study was done by administering the questionnaire to 40 respondents. The demographic variables of respondents namely gender, age, ethnicity and education were analysed using bar graphs and pie charts. The data was tested for normality and heteroscedasticity. The results showed that the assumptions were not violated. The study observed the effect of role conflict, role ambiguity, role overload and time stress on work tension and the influence of work tension on job satisfaction. The reliability analysis showed that all the constructs under investigation yielded an internal consistency reliability that is acceptable. Descriptive statistics were computed to summarise the data into usable information by making use of measures of central tendency. They were presented for each construct. The mean values for each construct was approximately neutral, which implies that many of the respondents neither agreed nor disagreed with the items. Regression and correlation analysis were undertaken to examine the effect of the various study constructs in line with the objectives of the study. The findings of the research depicted that there was a positive association between role conflict (RC), role ambiguity (RA), role overload (RO), time pressure (TP) on work tension (WT). The association between work tension (WT) and job satisfaction (JS) was found to be negative and significant. It was recommended among other things that the university management should put in place strategies to moderate RC, RA, RO, TP to reduce WT and job dissatisfaction.
M. Tech. (Department of Human Resource Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Job satisfaction; Job stress; Role conflict; Time pressure; University academics; Work tension; Dissertations, Academic -- South Africa.; Job stress.; Job satisfaction.; Universities and colleges -- Employees.